Analysis of nickel-copper metallic foam supercapacitor for electric vehicles with hybrid battery-supercapacitor energy storage system - Malburg, Leonardo Corrêa (2020)
Trabalho final de mestrado para obtenção do grau de mestre em Engenharia Eletrotécnica - Ramo de Energia